2017
DOI: 10.1093/fampra/cmx062
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of nocturnal leg cramps by primary care patients over the age of 60

Abstract: This study sheds light on the great diversity of therapeutic practices for cramps in outpatient care. Many of the treatments reported by patients have not previously been described in the medical literature. We recommend GPs to ask their patients about the treatments they take for cramps in order to make sure that they are safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…This result fits well with the conclusion of a recent cross-sectional study designed to identify more treatment options for this highly prevalent nonspecific disorder. 26 In a recent review, a pre-sleep stretching program combined with quinine use in NLC was proven to be ineffective, and a Cochrane review concluded that magnesium is unlikely to provide prophylaxis in older adults with NLC. 4 Due to conflicting evidence, the modest benefit and the additional risks of using quinine as a widely used treatment option increase the doubt about providing this drug.…”
Section: Discussionmentioning
confidence: 99%
“…This result fits well with the conclusion of a recent cross-sectional study designed to identify more treatment options for this highly prevalent nonspecific disorder. 26 In a recent review, a pre-sleep stretching program combined with quinine use in NLC was proven to be ineffective, and a Cochrane review concluded that magnesium is unlikely to provide prophylaxis in older adults with NLC. 4 Due to conflicting evidence, the modest benefit and the additional risks of using quinine as a widely used treatment option increase the doubt about providing this drug.…”
Section: Discussionmentioning
confidence: 99%
“…Idiopathic cramps notably include nocturnal leg cramps 2,15 . Although nocturnal muscle cramps occur at night, 20% of cases can have leg cramps primarily during the daytime 16 .…”
Section: Discussionmentioning
confidence: 99%
“…It was part of a larger study exploring the association between lifestyle and NLC. 21 We carried out a case-control study in 2013. The study consisted of a 6-month screening phase which was followed by an 11-month data collection phase.…”
Section: Methodsmentioning
confidence: 99%